Differential microglial dynamics and neuroinflammation underlying neuropathic pain in the central nervous system: comparative insights from spinal cord injury and compressive myelopathy models - Kubota, Arisa; Nakajima, Hideaki; Honjoh, Kazuya; Watanabe, Shuji; Takahashi, Ai; Matsumine, Akihiko (Frontiers in Cellular Neuroscience, 2026)
IntroductionNeuropathic pain (NeP) is a major complication of spinal cord disorders that is refractory to therapy and impairs quality of life. Acute neuroinflammatory responses occur after spinal cord injury (SCI), but chronic-phase microglia/macrophage (M/M) dynamics and their involvement in degenerative compressive myelopathy (DCM) are unclear. Brain M/M may contribute to persistent NeP; however, comparative analyses of SCI and DCM are lacking. The aim of this study was to investigate M/M activation and pain-related signaling dynamics in the spinal cord and brain, and their roles in chronic NeP following SCI and DCM.MethodsContusive SCI was induced in C57BL/6N mice. Chronic compression was modeled using ttw/ttw mice. Motor function was assessed using the Basso Mouse Locomotor Scale. Mechanical and thermal sensitivities were evaluated. M/M activation and pain-related molecules (p-p38, p-ERK1/2) were assessed in spinal and brain regions using immunohistochemical staining. Cytokine expression was analyzed using western blotting.ResultsSCI mice showed early M/M activation at the injured site with spread to the lumbar enlargement, paralleling mechanical and thermal hypersensitivity. In DCM, M/M activation increased with compression severity, but did not extend to the lumbar enlargement. Both models showed M/M and pain-related upregulation of molecules in the hippocampus and amygdala, and thalamic activation in acute SCI or moderate-to-severe compression. Pro-inflammatory cytokines peaked acutely in SCI and under moderate compression in DCM. Anti-inflammatory cytokine induction was limited in DCM.DiscussionDistinct neuroinflammatory patterns underlie chronic NeP in SCI and DCM. SCI shows M/M activation shifting from the injured site to the lumbar enlargement and limbic brain regions, consistent with chronic below-level pain. DCM shows localized M/M activation, but earlier hippocampal/amygdalar involvement, consistent with chronic at-level pain. These findings suggest pathology-specific therapeutic windows for targeting M/M-mediated neuroinflammation to prevent NeP.